The Impact of Intoxication on the Prognosis of High-Speed Motor Vehicle Accidents: A Tertiary Care Center Experience - Alqirnas, Muhannad; Aljarwan, Rafeef; Alhamadh, Moustafa; Khallaf, Sadeem; Alsomali, Faisal; Albaqami, Faris; AlMudaiheem, Najd; A. AlKhashan, Munira; Al Deeb, Mohammad (Archives of Academic Emergency Medicine, 2024)
Introduction: Several studies suggest a causal link between psychoactive agents and motor vehicle accidents (MVA). This study aimed to evaluate the impact of substance abuse and alcohol intoxication on the prognosis of high-speed MVA victims. Methods: This is a single-center retrospective cross-sectional study involving adult multiple trauma cases who were admitted to the emergency department for high-speed MVA and underwent toxicological screening. The cohort was conducted based on two main outcomes; the survival status and the neurological outcomes. Results: 894 patients with the mean age of 27.8 ± 9.24 (range:18-37) years were studied (97.9% male). The most common indicators of severity were car rollover and ejection from the car. 296 of the patients had severe traumatic brain injury (TBI). 622 of the patients had a positive toxicological screening, with benzodiazepines (51.2%) and alcohol (26.6%) being the most commonly abused substances. The mortality rate was 5.8% and 12.1% of the patients had unfavorable neurological outcomes upon discharge. On multivariate logistic regression, predictors of mortality among high-speed MVA victims were report of a death at the scene (adjusted odds ratio (aOR): 2.529; 95% confidence interval (CI): 1.026-6.232; p = 0.044), severe TBI, the presence of dilated pupils (aOR: 11.074; 95% CI: 1.293-94.812; p = 0.028), hypotension (aOR: 0.456; 95% CI: 0.227-0.916; p = 0.027), and hypoxia (aOR: 2.95; 95% CI: 1.46-5.95; p = 0.003). Predictors of unfavorable neurological outcomes were report of a death at the scene (aOR: 3.133; 95% CI: 1.445-6.791; p = 0.004), positive toxicology screening (aOR: 3.30; 95% CI:1.68-10.204; p = 0.038), severe TBI, the presence of hypoxia (aOR: 2.96; 95% CI:1.645-5.319; p = 0.000), hypotension (aOR: 0.437; 95% CI: 0.252-0.758; p = 0.003), and bleeding (aOR: 0.287; 95% CI: 0.164-0.501; p < 0.001). Conclusion: A concerning proportion of high-speed MVA victims had a positive toxicology screening. Although intoxication did not increase mortality of high-speed MVAs, it was a significant predictor of unfavorable neurological outcomes of survivors.